Peripheral nervous system in primates - Gładykowska-Rzeczycka , Judyta (Anthropological Review, 1974)
The structure of the lumbar plexus and the sacral one in 108 primates has been examined. It was found: 1. Starting from lower to higher forms a shifting of both plexuses toward the head (table 1, 2); 2. Changes in the number of nerves that form the plexuses and in the number of nerves that move away from plexus (table 2, 4); 3. Three varieties in structure of the sacral plexus: a shortened, intermediate and elongated variety which mainly depend on the somatic structure (table 5); 4. Three types of joining the lumbar plexus to the sacral one and several varieties within each type (table 6); 5. That the way the nerves move away from the plexus con- stitutes no distinct classifying characteristic; 6. An asymmetry although a distinct one has no classifying value; 7. Absence of sex dimorphism; 8. That spider-monkeys (Ateles) from the sub-order of broadnosed monkeys in the structure of their plexuses strictly link to higher forms — Homonoidea.